INVESTIGATION OF OPERATIONAL PROPERTIES POLYMER MATERIALS - S. Ibragimov (Journals Park Publishing, 2024)
This article discusses the procedure for determining the basic laws of dry friction and determining the sliding friction coefficient of polymer materials, as well as measuring the coefficient of friction and wear resistance of polymer materials.
Keywords: polymer materials, friction, sliding, wear resistance, high strength, chemical structure.